Carbon fiber base material for fuel cell, preparation method of carbon fiber base material, raw carbon paper and preparation method of raw carbon paper

By adding microfibrinated cellulose and pre-oxygen wire pulp to the slurry of the carbon fiber substrate, the problems of low physical strength of the carbon fiber substrate and degraded mechanical properties of carbon fiber paper are solved, and the preparation of carbon fiber substrate and carbon paper with high mechanical strength and conductivity are realized.

CN119531187AActive Publication Date: 2025-02-28LINENG NEW ENERGY TECH (BEIJING) CO LTD

Patent Information

Application Number
CN202411705568.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-28
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

The physical strength of the carbon fiber substrate for fuel cell gas diffusion layer is low, resulting in poor preparation performance, and the traditional surface glue-adding method reinforces the carbon fiber substrate to reduce the mechanical properties of carbon-grown paper.

Method used

Microfibrillated cellulose (MFC) or a mixture of MFC and pre-oxygen wire pulp is used as reinforcement fibers, and then mixed with carbon fiber and dispersant is mixed with wet molding process to prepare carbon fiber substrates to improve their dispersion, mechanical strength and electrical conductivity.

Benefits of technology

The physical strength and conductivity of the carbon fiber substrate are improved, and the mechanical properties and conductivity of carbon-generated paper are ensured to meet the requirements of the gas diffusion layer of the fuel cell, and the process is simple and suitable for mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119531187A_ABST
    Figure CN119531187A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of fuel cells, in particular to a carbon fiber base material for a fuel cell, a preparation method of the carbon fiber base material, raw carbon paper and a preparation method of the raw carbon paper. The preparation method of the carbon fiber base material comprises the following steps: S1, adopting MFC or a mixture of MFC and pre-oxidized fiber pulp as reinforcing fibers, mixing the reinforcing fibers with water, and pulping to obtain premixed slurry; s2, uniformly mixing carbon fibers, the premixed slurry and a dispersing agent to obtain mixed slurry, molding the mixed slurry by adopting a wet molding process, and drying to obtain the carbon fiber base material. The MFC or the mixture of the MFC and the pre-oxidized fiber pulp is used as the reinforcing fiber, and the reinforcing fiber is pulped and then mixed with the carbon fiber and the dispersing agent to prepare the carbon fiber base material, so that the dispersity of the carbon fiber and the mechanical strength and conductivity of the carbon fiber base material in the wet forming process can be improved; and the negative influence on the subsequent preparation of the raw carbon paper is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fuel cells, and in particular to a carbon fiber substrate for fuel cells and a preparation method thereof, raw carbon paper and a preparation method thereof. Background Art

[0002] The working principle of the proton exchange membrane fuel cell (PEMFC) is that the fuel gas H2 passes through the flow channel provided by the gas diffusion layer to reach the anode catalyst layer, where an oxidation reaction occurs to generate protons H + and electrons, and at the same time, O2 reaches the cathode catalyst layer after passing through the gas diffusion layer. With the participation of the cathode catalyst, it undergoes a cathode reduction reaction with the protons passing through the proton exchange membrane and the electrons flowing back to the battery from the external circuit to generate water. The gas diffusion layer is an important component in the proton exchange membrane fuel cell. It supports the catalyst layer and provides a channel for the reaction gas and the product water. At the same time, it must have relatively good electrical conductivity and corrosion resistance under electrochemical reactions. Based on the requirements of the gas diffusion layer for conductivity, gas and water transmission, thermal conductivity, and high strength, the material currently used in the gas diffusion layer of fuel cells is carbon material. Carbon material has both high conductivity and strong anti-corrosion performance and low cost, which is an advantage that other materials do not have. However, carbon material is brittle in nature, which is not conducive to molding and processing. The control of its microstructure is also a relatively large difficulty. Therefore, the research on the process method of using carbon material to prepare a gas diffusion layer with excellent performance has become the focus of research.

[0003] Carbon fiber substrate is the first choice for gas diffusion layer materials because of its mature manufacturing process and stable performance. At present, the preparation of carbon fiber substrate for fuel cell gas diffusion layer is prepared by wet molding method using carbon fiber or mixing other fibers into carbon fiber. Carbon fiber is generally a fiber that has been carbonized or even graphitized at high temperature, so it is impossible to separate and pulverize it in the pulping stage like plant fiber or polymer fiber. In addition, carbon fiber rarely contains non-carbon elements, has a smooth surface, low surface energy, few active groups, poor hydrophilicity, and is difficult to disperse, which will lead to poor dispersion of carbon fiber in water and poor bonding ability between carbon fibers, thereby reducing the mechanical properties of carbon fiber substrate for gas diffusion layer. The carbon fiber substrate for the gas diffusion layer of the fuel cell must have appropriate mechanical strength for the subsequent gas diffusion layer preparation process, so that the gas diffusion layer can independently support the catalyst layer, thereby stabilizing the entire electrode structure. At present, the mechanical strength of the carbon fiber substrate is mainly enhanced by adding a binder to the slurry or applying a sizing agent to the surface. However, due to its own characteristics, the addition of the binder to the slurry will affect the dispersion effect of the carbon fiber and the uniformity characteristics of the carbon fiber substrate; the method of surface sizing to enhance the carbon fiber substrate will cause poor subsequent impregnation due to the presence of the binder on the surface of the carbon fiber substrate, low resin sizing, and poor mechanical properties of the raw carbon paper, thereby affecting the assembly performance of the gas diffusion layer. Therefore, it is of great significance to provide a method for preparing a carbon fiber substrate and raw carbon paper for the gas diffusion layer of a fuel cell with high physical strength, good conductivity, and good carbon fiber dispersion effect.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The first purpose of the present invention is to provide a method for preparing a carbon fiber substrate for a fuel cell, so as to solve the technical problems that the physical strength of the carbon fiber substrate for the gas diffusion layer of the fuel cell is low, resulting in poor preparation performance of the gas diffusion layer, and the traditional surface sizing method for reinforcing the carbon fiber substrate will lead to a decrease in the mechanical properties of raw carbon paper; the present invention adopts microfibrillated cellulose (MFC) or a mixture of MFC and pre-oxidized silk pulp as reinforcing fiber, and after pulping, it is mixed with carbon fiber and a dispersant to prepare a carbon fiber substrate, which can improve the dispersibility of carbon fiber in the wet molding process as well as the mechanical strength and conductivity of the carbon fiber substrate, and will not have a negative impact on the subsequent preparation of raw carbon paper.

[0006] The second object of the present invention is to provide a carbon fiber substrate for a fuel cell, which is prepared by the method for preparing a carbon fiber substrate for a fuel cell as described above.

[0007] The third purpose of the present invention is to provide a method for preparing raw carbon paper for fuel cells, which adopts the carbon fiber substrate as described above, and is obtained by impregnation with resin, drying, hot pressing and curing, and carbonization and graphitization. The raw carbon paper prepared by the method of the present invention has high mechanical strength and low resistivity, and the preparation process is simple, which is convenient for mass production.

[0008] The fourth object of the present invention is to provide a raw carbon paper for fuel cells, which is prepared by the method for preparing raw carbon paper for fuel cells as described above.

[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted: A method for preparing a carbon fiber substrate for a fuel cell comprises the following steps: S1. Using MFC or a mixture of MFC and pre-oxidized silk pulp as reinforcing fiber, the reinforcing fiber is mixed with water for beating to obtain a premixed slurry; S2. The carbon fiber, the premixed slurry and the dispersant are uniformly mixed to obtain a mixed slurry, and the mixed slurry is formed by a wet forming process and then dried to obtain the carbon fiber substrate.

[0010] A carbon fiber substrate for a fuel cell is prepared by the method for preparing the carbon fiber substrate for a fuel cell as described above.

[0011] A method for preparing raw carbon paper for a fuel cell comprises the following steps: The raw carbon paper is obtained by using the carbon fiber substrate for fuel cells as described above, and performing resin impregnation, drying, hot pressing and solidification, and carbonization and graphitization treatment.

[0012] A raw carbon paper for fuel cells is prepared by the method for preparing the raw carbon paper for fuel cells as described above.

[0013] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention adds MFC or a mixture of MFC and pre-oxidized silk pulp as reinforcing fiber to the slurry, and utilizes the filament separation effect of MFC after pulping to expose more hydrogen bonds of the MFC, which are distributed between carbon fibers and build bridges between carbon fibers. The carbon fibers with poor binding ability are more tightly bound due to the presence of microfibrillated cellulose, and the pre-oxidized silk pulp can be used as a button for overlapping carbon fibers, thereby improving the physical strength of the carbon fiber substrate.

[0014] (2) The surface of MFC carries the same negative charge as the carbon fiber. Since charges of the same kind repel each other, the fibers are well dispersed. Compared with the traditional method of reinforcing the carbon fiber substrate, the substrate prepared by the method of the present invention has higher uniformity, simple process flow and high feasibility.

[0015] (3) After pulping, MFC can form a denser network structure, which can serve as a supporting structure for the resin. In addition, the specific surface area of ​​MFC increases after pulping, exposing more hydrophilic groups on the surface of the carbon fiber substrate, enhancing the adsorption of the resin, improving the subsequent impregnation properties, and increasing the amount of resin applied. In addition, the larger specific surface area can provide more active sites and interfacial interactions with conductive substances. In addition, the added MFC has a certain pore structure, which increases the adsorption of conductive substances, thereby improving the mechanical strength and conductivity of the raw carbon paper.

[0016] (4) The carbon fiber substrate prepared by the present invention has high mechanical strength and high uniformity, which can meet the requirements for the subsequent preparation of raw carbon paper. In addition, the raw carbon paper obtained after resin impregnation, curing, and carbonization and graphitization treatment has good mechanical properties and high conductivity, which can meet the requirements of the gas diffusion layer of the fuel cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0018] Figure 1 Microscope pictures of MFC before and after treatment under different conditions provided by the embodiment of the present invention, wherein a is unpulped MFC (50X), b is MFC after water-pulping (500X), c is MFC after immersion treatment in a pretreatment solution and freeze-drying, and then water-pulping (500X), d is MFC after ultrasonic treatment in water and pulping (100X), e and f are MFC after ultrasonic treatment in a pretreatment solution and freeze-drying, and then water-pulping (e 200X, f 500X); Figure 2 Microscope pictures of carbon fiber substrates provided for different embodiments and comparative examples of the present invention, wherein a is comparative example 1 (200X), b is example 1 (200X), c is example 5 (200X), d is example 6 (200X), and e is example 4 (200X); Figure 3 These are microscope pictures of carbon fiber substrates impregnated with pure resin in different embodiments and comparative examples of the present invention, wherein a is comparative example 3 (200X), b is example 7 (200X), and c is example 9 (200X); Figure 4 These are microscope pictures of carbon fiber substrates impregnated with resin containing conductive substances in different embodiments and comparative examples of the present invention, wherein a is comparative example 4 (200X), and b is embodiment 10 (200X); Figure 5 Microscope pictures of raw carbon paper prepared by impregnating pure resin into carbon fiber substrate in different embodiments and comparative examples of the present invention, wherein a is comparative example 3 (200X), b is example 7 (200X), and c is example 9 (500X); Figure 6 The microscope pictures of raw carbon paper prepared by impregnating a carbon fiber substrate with a resin containing a conductive substance in different embodiments and comparative examples of the present invention, wherein a is comparative example 4 (200X), and b is embodiment 10 (200X). DETAILED DESCRIPTION

[0019] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0020] A first aspect of the present invention provides a method for preparing a carbon fiber substrate for a fuel cell, comprising the following steps: S1. Using MFC or a mixture of MFC and pre-oxidized silk pulp as reinforcing fiber, the reinforcing fiber is mixed with water for beating to obtain a premixed slurry; S2. The carbon fiber, the premixed slurry and the dispersant are uniformly mixed to obtain a mixed slurry, and the mixed slurry is formed by a wet forming process and then dried to obtain a carbon fiber substrate.

[0021] Microfibrillated cellulose (MFC) refers to a chaotic network composed of a large number of linear nano-scale microfibers. It is a cellulose derivative. MFC has the characteristics of high specific surface area, high strength, high crystallinity, etc. Compared with ordinary cellulose, MFC has a large specific surface area and exposes a large number of polar hydroxyl groups. During the preparation and processing of microfibrillated cellulose, the fiber surface carries a certain negative charge. After adding the slurry, due to the principle of mutual repulsion between ions of the same charge, the fibers in the slurry will repel each other with the negatively charged carbon fibers, so that the fibers in the slurry can be dispersed with each other, thereby improving the uniformity of the slurry and improving its physical properties. In addition, MFC has a large crystallinity, water retention value, specific surface area, stability, and dispersibility, which can improve the physical properties of paper. When preparing carbon fiber substrates for fuel cells, it can increase the hydrogen bonding effect between carbon fibers through the hydration between hydroxyl groups of microfibrillated cellulose, improve the bonding force of the fibers, and directly improve the physical strength of the carbon fiber substrate. This strength can meet the requirements of the impregnation and curing process.

[0022] The present invention adds MFC or a mixture of MFC and preoxidized silk pulp as reinforcing fiber in the slurry, utilizes the fiber separation and brooming effect after MFC beating to expose more hydrogen bonds, distribute them between carbon fibers, build bridges between carbon fibers, and make carbon fibers with poor binding ability more tightly bound due to the presence of microfibrillated cellulose, thereby improving the binding physical strength of the carbon fiber substrate, and the preoxidized silk pulp can be used as a button for overlapping carbon fibers, which can bind the overlap of carbon fibers and carbon fibers, further improving their physical strength. The preoxidized silk pulp is supplemented with overlapping on the original structure, and the conductivity of the preoxidized silk pulp is improved after carbonization, which optimizes the conductive network of raw carbon paper, making the raw carbon paper more conductive. The synergistic effect of MFC and preoxidized silk pulp can not only significantly improve the mechanical strength of the carbon fiber substrate and raw carbon paper, but also improve the conductivity of raw carbon paper.

[0023] The purpose of the present invention of beating the reinforcing fibers before mixing is to make the MFC form a denser network structure, which serves as a supporting structure for the resin, increases the specific surface area of ​​the MFC to provide more active sites and interface interactions with conductive substances, and at the same time exposes more hydrophilic groups on the surface of the carbon fiber substrate, thereby increasing its adsorption of conductive substances and resins, thereby improving the mechanical strength and conductivity of the raw carbon paper.

[0024] Depend on Figure 1As can be seen from Figures a and b, the unbeaten MFC fibers present a relatively complete and slender shape, with a certain length and width, relatively uniform length distribution, relatively independent fibers, no obvious interweaving and entanglement, smooth fiber surface, no obvious damage and breakage marks, and disorderly fiber arrangement without specific direction and regularity; while the MFC after beating has a certain degree of breakage and thinning, and the fiber surface is worn and fluffed, the surface becomes rough, and the specific surface area increases, which is caused by the mechanical force during the beating process. The fiber arrangement becomes more disordered, and the fibers have been intertwined and entangled with each other, forming a more complex network structure.

[0025] In some specific embodiments of the present invention, in step S1, before preparing the premixed slurry, the step of performing a first pretreatment or a second pretreatment on the reinforcing fibers is further included, that is, the premixed slurry is prepared using the pretreated reinforcing fibers; The first pretreatment step includes: preparing a pretreatment solution containing protonic acid, organic solvent and water, placing the reinforcing fiber in the pretreatment solution for immersion, separating the solid and liquid, and freeze-drying; or placing the reinforcing fiber in the pretreatment solution and performing ultrasonic treatment, and after the ultrasonic treatment, separating the solid and liquid, and freeze-drying; The second pretreatment step includes: placing the reinforcing fiber in water and performing ultrasonic treatment, and after the ultrasonic treatment, performing solid-liquid separation and freeze-drying.

[0026] Using the proton acid in the pretreatment liquid to dope the microfibrillated cellulose with proton acid can protonate the functional groups such as hydroxyl groups in the microfibrillated cellulose, which can increase the conductivity of the substrate; the microfibrillated cellulose after ultrasonic treatment is more refined after beating, and has a stronger bonding force with the carbon fiber. Figure 1 As shown in Figures b and c, the morphology of MFC after pulping treated with proton acid is not much different from that of MFC after direct pulping. Figure 1 It can be seen from Figures d, e and f that the MFC treated with ultrasonic activation in water or in a pretreatment solution exhibits a higher degree of filament fibrillation after pulping, with more fiber filaments exposed, better fiber swelling, rougher surface and more fluffing, which brings the fiber network of MFC to its extreme state and achieves the best application performance.

[0027] In the present invention, protonation treatment can improve the conductivity of the substrate, ultrasonic treatment can improve the degree of fibrillation of the MFC after pulping, and improve the bonding strength between the MFC and the carbon fiber. Ultrasonic treatment in the pretreatment solution can achieve better synergistic effects.

[0028] The organic solvent in the pretreatment solution of the present invention is mainly used to adjust the polarity and solubility of the reaction system so that it has good proton transfer ability.

[0029] In some preferred embodiments of the present invention, before preparing the premixed slurry, the reinforcing fiber is subjected to a first pretreatment, and the first pretreatment specifically includes the following steps: placing the MFC in a pretreatment liquid, ultrasonically activating it for 40-60 minutes, then adding preoxidized silk pulp, continuing ultrasonic treatment for 30-60 minutes, solid-liquid separation, and freeze-drying to obtain the pretreated reinforcing fiber.

[0030] After the MFC is ultrasonically activated in the pretreatment liquid and then blended with the preoxidized silk pulp, the obtained carbon fiber substrate preoxidized silk pulp has a larger loading amount, which can better optimize the conductive network structure of the raw carbon paper, making the raw carbon paper have better conductive properties. The present invention improves the conductive properties of the carbon fiber substrate by adding pretreated microfibrillated cellulose and preoxidized silk pulp to the slurry. This is because the hydroxyl groups of the pretreated microfibrillated cellulose are protonated, which increases the conductivity of the substrate; and further improves the physical strength of the carbon fiber substrate. This is because the ultrasonically treated microfibrillated cellulose is more refined after beating and has a stronger bonding force with the carbon fiber. Second, the preoxidized silk pulp with a certain particle size and a certain length becomes the "button" of the carbon fiber overlap point.

[0031] In some embodiments, typically but not limitatively, for example, before adding the pre-oxidized silk pulp, the ultrasonic activation time of MFC in the pretreatment liquid can be any point value among 40min, 45min, 50min, 55min, 60min, or a range value consisting of any two point values; after adding the pre-oxidized silk pulp, the time for continuing the ultrasonic treatment can be any point value among 30min, 35min, 40min, 45min, 50min, 55min, 60min, or a range value consisting of any two point values.

[0032] In some specific embodiments of the present invention, the ultrasonic power of the first pretreatment and the second pretreatment is 250-300W, for example, can be independently selected from any point value of 250W, 260W, 270W, 280W, 290W, 300W or a range consisting of any two point values; the treatment temperature is 30-50°C, for example, can be independently selected from any point value of 30°C, 35°C, 40°C, 45°C, 50°C or a range consisting of any two point values.

[0033] In some specific embodiments of the present invention, H in the pretreatment solution + The concentration is 0.15-2 mol / L, for example, it can be any point value among 0.15 mol / L, 0.5 mol / L, 1 mol / L, 1.5 mol / L, 2 mol / L or a range value consisting of any two point values; by + The concentration of protonic acid controls the dosage.

[0034] In some specific embodiments of the present invention, the protonic acid used includes hydrochloric acid and / or sulfuric acid.

[0035] In some specific embodiments of the present invention, the organic solvent used includes ethanol or acetone, and its main function is to adjust the polarity and solubility of the system and improve the proton transfer capacity.

[0036] In some specific embodiments of the present invention, in the pretreatment liquid, the mass ratio of the organic solvent to water is 1:1-3:1, for example, it can be any point value among 1:1, 1.5:1, 2:1, 2.5:1, 3:1 or a range value consisting of any two point values; to avoid impurities, as an example, the water used is pure water.

[0037] In some specific embodiments of the present invention, in step S1, the beating speed is 5-30m / s (linear speed), for example, it can be any point value among 5m / s, 10m / s, 15m / s, 20m / s, 25m / s, 30m / s or a range value consisting of any two point values; the beating time is 5-20min, for example, it can be any point value among 5min, 10min, 15min, 20min or a range value consisting of any two point values. The beating treatment can cause the MFC to break and refine, the fiber to have surface wear and fluffing, the surface to become rough, the specific surface area to increase, the fibers to be intertwined and entangled with each other, to form a complex network structure, and to improve its bonding strength with the carbon fiber.

[0038] In some specific embodiments of the present invention, before step S2, the step of performing a third pretreatment on the carbon fiber is also included, that is, the carbon fiber after the third pretreatment is mixed with a premixed slurry and a dispersant to prepare a mixed slurry, and the third pretreatment includes the following steps: the carbon fiber is subjected to air pre-oxidation treatment in an air atmosphere, and the air pre-oxidation treatment temperature is 300-600°C, for example, it can be any point value among 300°C, 400°C, 500°C, 600°C or a range value composed of any two point values; the treatment time is 30-150min, for example, it can be any point value among 30min, 60min, 90min, 120min, 150min or a range value composed of any two point values.

[0039] In some specific embodiments of the present invention, in step S2, the stirring speed of the mixing process is 5-30 m / s (linear speed), for example, it can be any point value among 5 m / s, 10 m / s, 15 m / s, 20 m / s, 25 m / s, 30 m / s or a range value consisting of any two point values; the mixing time is 5-30 min, for example, it can be any point value among 5 min, 10 min, 20 min, 30 min or a range value consisting of any two point values.

[0040] In some specific embodiments of the present invention, in step S2, the mixed slurry is prepared under the conditions of 20-30° C. and 20%-50% relative humidity.

[0041] In some specific embodiments of the present invention, in step S2, the mass concentration of carbon fiber in the mixed slurry is 0.1%-0.5%, for example, it can be any point value among 0.1%, 0.2%, 0.3%, 0.4%, 0.5% or a range value consisting of any two point values.

[0042] In some specific embodiments of the present invention, in step S2, the mass percentage of MFC in carbon fiber is 5%-10%, for example, it can be any point value of 5%, 6%, 7%, 8%, 9%, 10%, or a range value consisting of any two point values. If the amount of MFC is too little, the reinforcement effect is not good, and if it is too much, the conductivity of the carbon fiber substrate will decrease. Therefore, the amount range of MFC needs to be reasonably controlled.

[0043] In some specific embodiments of the present invention, in step S2, the mass percentage of pre-oxidized silk pulp to carbon fiber is 0%-10%, for example, it can be any point value among 0%, 2%, 4%, 6%, 8%, 10% or a range value consisting of any two point values.

[0044] In some specific embodiments of the present invention, in step S2, the mass concentration of the dispersant in the mixed slurry is 0.1%-0.5%, for example, it can be any point value among 0.1%, 0.2%, 0.3%, 0.4%, 0.5% or a range value consisting of any two point values.

[0045] In some specific embodiments of the present invention, in step S2, the dispersant includes at least one of polysorbate, polyurethane, and hydroxypropyl cellulose.

[0046] The second aspect of the present invention provides a carbon fiber substrate for a fuel cell, which is prepared by the preparation method of the carbon fiber substrate for a fuel cell described in any one of the above embodiments. The carbon fiber substrate provided by the present invention has good uniformity and high mechanical strength, can meet the subsequent preparation requirements of raw carbon paper, and compared with the traditional reinforcement method, improves the conductivity of the carbon fiber substrate and raw carbon paper.

[0047] A third aspect of the present invention provides a method for preparing raw carbon paper for a fuel cell, comprising the following steps: The carbon fiber substrate described in the above embodiment is used, and is subjected to resin impregnation, drying, hot pressing and curing, and carbonization and graphitization treatment to obtain raw carbon paper.

[0048] In some specific embodiments of the present invention, the impregnating resin may be a phenolic resin or a phenolic resin containing a conductive substance. For example, the conductive substance may be graphite powder with a particle size of 0.5-30 μm. In some embodiments, the phenolic resin accounts for 15wt%-25wt% of the impregnating solution; if the conductive substance is contained, the conductive substance accounts for 5wt%-20% of the impregnating solution.

[0049] In some specific embodiments of the present invention, the pressure of hot pressing curing is 2.0-4.0MPa, for example, it can be any point value among 2.0MPa, 2.5MPa, 3.0MPa, 3.5MPa, and 4MPa, or a range value consisting of any two point values; the temperature is 120-200°C, for example, it can be any point value among 120°C, 150°C, 180°C, and 200°C, or a range value consisting of any two point values; the time is 2-10min, for example, it can be any point value among 2min, 4min, 6min, 8min, and 10min, or a range value consisting of any two point values.

[0050] In some specific embodiments of the present invention, the temperature of the carbonization and graphitization treatment is 1600-2200°C, for example, it can be any point value among 1600°C, 1700°C, 1900°C, 2200°C or a range value consisting of any two points; the treatment time is 60-120min.

[0051] The fourth aspect of the present invention provides a raw carbon paper for a fuel cell, which is prepared by the method for preparing raw carbon paper for a fuel cell described in any one of the above embodiments. Compared with the raw carbon paper obtained by the traditional method, the raw carbon paper provided by the present invention has significantly improved tensile strength and bending strength, and significantly reduced plane resistivity and vertical resistivity, and improved mechanical strength and conductivity.

[0052] The following is a detailed description of some embodiments of the present invention in conjunction with specific examples. The raw materials used in the examples can be purchased from the market unless otherwise specified.

[0053] Example 1 This embodiment provides a carbon fiber substrate for a fuel cell, and the preparation steps are as follows: S1. The MFC was put into water and premixed and slurried under the condition of a stirring line speed of 20 m / s for a slurry time of 10 min to obtain a premixed slurry; Carbon fiber pretreatment: The prepared short-cut carbon fiber is subjected to air oxidation treatment in a muffle furnace. The length of the short-cut carbon fiber is 6 mm, the treatment temperature is 500°C, and the treatment time is 120 min. S2. At a temperature of 25°C and a relative humidity of 40%, the pretreated carbon fiber, premixed slurry and polysorbate were mixed, and the stirring line speed was 10 m / s for 5 minutes to mix the slurry evenly to obtain a mixed slurry in which the carbon fiber and microfibrillated cellulose were evenly dispersed, wherein the addition amount of polysorbate was 0.1wt% of the mixed slurry, the addition amount of carbon fiber was 0.1wt% of the mixed slurry, and the addition amount of MFC was 5% of the mass of the carbon fiber; The mixed slurry is formed by a wet forming process and dried to obtain a carbon fiber substrate for a fuel cell.

[0054] Example 2 The preparation method of Example 2 is similar to that of Example 1, with the only difference being that the amount of MFC added is 10% of the mass of the carbon fiber, and the other conditions are the same as those of Example 1.

[0055] Example 3 This embodiment provides a carbon fiber substrate for a fuel cell, and the preparation steps are as follows: S1. The MFC and pre-oxidized silk pulp were put into water, premixed and beaten under stirring line speed of 20 m / s, and the beating time was 10 min to obtain a premixed slurry; Carbon fiber pretreatment: The prepared short-cut carbon fiber is subjected to air oxidation treatment in a muffle furnace. The length of the short-cut carbon fiber is 6 mm, the treatment temperature is 500°C, and the treatment time is 120 min. S2. At a temperature of 25°C and a relative humidity of 40%, the pretreated carbon fiber, premixed slurry and polysorbate were mixed, and the stirring line speed was 10 m / s for 5 minutes to mix the slurry evenly to obtain a mixed slurry in which the carbon fiber, microfibrillated cellulose and preoxidized silk pulp were evenly dispersed, wherein the addition amount of polysorbate was 0.1wt% of the mixed slurry, the addition amount of carbon fiber was 0.1wt% of the mixed slurry, the addition amount of MFC was 5% of the mass of the carbon fiber, and the addition amount of preoxidized silk pulp was 8% of the mass of the carbon fiber; The mixed slurry is formed by a wet forming process and dried to obtain a carbon fiber substrate for a fuel cell.

[0056] Example 4 This embodiment provides a carbon fiber substrate for a fuel cell, and the preparation steps are as follows: S1. Pretreatment of reinforcing fibers: a pretreatment solution is prepared by using ethanol, hydrochloric acid and pure water, wherein the concentration of hydrochloric acid in the pretreatment solution is 1 mol / L, and the mass ratio of ethanol to pure water is 1:1; MFC is placed in the pretreatment solution, ultrasonically activated for 40 min at 30°C and an ultrasonic power of 250 W, and then preoxidized silk pulp is added, and ultrasonic treatment is continued for 60 min under the same conditions, and then filtered and freeze-dried to obtain the pretreated reinforcing fibers; Beating: the pretreated reinforcing fibers are put into water, and premixed and beaten at a stirring line speed of 20 m / s for 10 min to obtain a premixed slurry; Carbon fiber pretreatment: The prepared short-cut carbon fiber is subjected to air oxidation treatment in a muffle furnace. The length of the short-cut carbon fiber is 6 mm, the treatment temperature is 500°C, and the treatment time is 120 min. S2. At a temperature of 25°C and a relative humidity of 40%, the pretreated carbon fiber, premixed slurry and polysorbate were mixed, and the stirring line speed was 10 m / s for 5 minutes to mix the slurry evenly to obtain a mixed slurry in which the carbon fiber, microfibrillated cellulose and preoxidized silk pulp were evenly dispersed, wherein the addition amount of polysorbate was 0.1wt% of the mixed slurry, the addition amount of carbon fiber was 0.1wt% of the mixed slurry, the addition amount of MFC was 5% of the mass of the carbon fiber, and the addition amount of preoxidized silk pulp was 8% of the mass of the carbon fiber; The mixed slurry is formed by a wet forming process and dried to obtain a carbon fiber substrate for a fuel cell.

[0057] Example 5 The preparation method of Example 5 is similar to that of Example 4, with the only difference being that when pretreating the reinforcing fibers, no ultrasound is applied, and the reinforcing fibers are only immersed in the pretreatment liquid and then filtered and freeze-dried to obtain the pretreated reinforcing fibers; the remaining preparation conditions are the same as those of Example 4.

[0058] Example 6 The preparation method of Example 6 is similar to that of Example 4, with the only difference being that when pretreating the reinforcing fibers, the pretreatment liquid is replaced with pure water, and the other conditions are the same as those of Example 4.

[0059] Example 7 This embodiment provides a raw carbon paper for a fuel cell, and the preparation steps are as follows: The carbon fiber substrate prepared in Example 1 was impregnated with phenolic resin, the concentration of the phenolic resin in the impregnating solution was 25wt%, and after drying, it was hot-pressed and cured at 3.0MPa and 150°C for 10min, and then carbonized and graphitized at 1900°C for 60min under nitrogen atmosphere protection to obtain raw carbon paper.

[0060] Example 8 This embodiment provides a raw carbon paper for a fuel cell. The raw carbon paper is prepared using the carbon fiber substrate prepared in Example 3. The preparation conditions of the raw carbon paper are the same as those in Example 7.

[0061] Example 9 This embodiment provides a raw carbon paper for a fuel cell. The raw carbon paper is prepared using the carbon fiber substrate prepared in Embodiment 4. The preparation conditions of the raw carbon paper are the same as those in Embodiment 7.

[0062] Example 10 This embodiment provides a raw carbon paper for a fuel cell, which uses the carbon fiber substrate prepared in Example 4 to impregnate a phenolic resin impregnation solution containing graphite powder, wherein the concentration of the phenolic resin is 25wt%, the concentration of the graphite powder is 10%, and the particle size of the graphite powder is 10μm; the other process conditions are the same as those in Example 9.

[0063] Embodiment 11 This embodiment provides a raw carbon paper for a fuel cell. The raw carbon paper is prepared using the carbon fiber substrate prepared in Example 5. The preparation conditions of the raw carbon paper are the same as those in Example 7.

[0064] Example 12 This embodiment provides a raw carbon paper for a fuel cell. The raw carbon paper is prepared using the carbon fiber substrate prepared in Example 6. The preparation conditions of the raw carbon paper are the same as those in Example 7.

[0065] Comparative Example 1 This comparative example provides a carbon fiber substrate for a fuel cell. The difference from Example 1 is that no MFC premix slurry is added. The specific preparation steps are as follows: S1. Carbon fiber pretreatment: The chopped carbon fiber prepared in advance is subjected to air oxidation treatment in a muffle furnace, the length of the chopped carbon fiber is 6 mm, the treatment temperature is 500°C, and the treatment time is 120 min; S2. Mix the pretreated carbon fiber and polysorbate at a temperature of 25°C and a relative humidity of 40%, stir and mix for 5 minutes at a stirring line speed of 10 m / s, and mix the slurries evenly to obtain a mixed slurry in which the carbon fiber is evenly dispersed, wherein the amount of polysorbate added is 0.1wt% of the mixed slurry, and the amount of carbon fiber added is 0.1wt% of the mixed slurry; The mixed slurry is formed by a wet forming process and dried to obtain a carbon fiber substrate for a fuel cell.

[0066] Comparative Example 2 After the carbon fiber substrate is prepared according to the method in Comparative Example 1, the surface is sizing for reinforcement. The sizing process is: dextrin is added with water to make a slurry, which is applied on the carbon fiber substrate and dried. The sizing amount is 3.0 g / m2 .

[0067] Comparative Example 3 This embodiment provides a raw carbon paper for a fuel cell. The raw carbon paper is prepared using the carbon fiber substrate in Comparative Example 1. The preparation conditions of the raw carbon paper are the same as those in Example 7.

[0068] Comparative Example 4 This embodiment provides a raw carbon paper for a fuel cell. The raw carbon paper is prepared using the carbon fiber substrate in Comparative Example 1. The preparation conditions of the raw carbon paper are the same as those in Example 10.

[0069] Comparative Example 5 This embodiment provides a raw carbon paper for a fuel cell. The raw carbon paper is prepared using the carbon fiber substrate reinforced by sizing in Comparative Example 2. The preparation conditions of the raw carbon paper are the same as those in Example 7.

[0070] Test example (1) The carbon fiber substrates prepared in Examples 1, 4, 5, 6 and Comparative Example 1 were observed under a microscope. Figure 2 As shown, in Comparative Example 1, in which no MFC is added to prepare the carbon fiber substrate, the carbon fibers are relatively clear, and only the carbon fibers overlap each other (Figure a); in Example 1, in which MFC is added to prepare the carbon fiber substrate, there is an approximately transparent MFC fiber network connection between the carbon fibers (Figure b); in Example 5, there is no significant difference between the carbon fiber substrate prepared by immersing the reinforcing fibers in a pretreatment solution containing a protonic acid and the carbon fiber substrate prepared by direct pulping in Example 1 (Figures b and c); in Example 6 and Example 4, the carbon fiber substrates prepared by ultrasonic activation treatment with MFC form a slightly increased MFC fiber network, and the carbon fiber substrate formed by combining the two methods has relatively more transparent MFC network connections (Figures d and e). This is because there are a large number of hydroxyl groups on the surface of the MFC molecular chain after pulping, the reaction activity is increased, and the mutual connection with the carbon fibers is increased. Ultrasonic activation increases this phenomenon, thereby further increasing the mechanical strength of the carbon fiber substrate.

[0071] (2) The amount of glue applied to the carbon fiber substrate after impregnation and drying in Examples 7, 9, 10 and Comparative Examples 3 and 4 was observed under a microscope. Figure 3 and Figure 4 As shown, compared with the carbon fiber substrate without MFC, the carbon fiber substrate with MFC added has relatively more glue, and the carbon fiber substrate with pretreated MFC and preoxidized silk pulp has more glue, and the corresponding conductive material adsorption is also more. This is because the complex network structure of MFC and the increase of its surface active groups improve the adsorption of resin and conductive substances.

[0072] (3) The raw carbon papers obtained in Examples 7, 9, 10 and Comparative Examples 3 and 4 were observed under a microscope. Figure 5 and Figure 6 As shown, compared with the raw carbon paper without MFC, the raw carbon paper with MFC has more residual carbon in resin, and the raw carbon paper with MFC after pretreatment has more residual carbon, and the corresponding residual carbon in the resin containing conductive substances also increases.

[0073] (4) The mechanical strength and resistivity of the carbon fiber substrates prepared in Examples 1-6 and Comparative Examples 1 and 2 were tested in accordance with the national standard GB / T20042.7-2014: "Proton Exchange Membrane Fuel Cell Part 7: Carbon Paper Property Test Method". The uniformity test of the carbon fiber substrate was carried out in accordance with the corporate standard Q / CZSO13-1997 "ZDD-1 Paper Uniformity Tester". The test results are shown in Table 1.

[0074] Table 1

[0075] It can be seen from the data in Table 1 that the uniformity of the carbon fiber substrate is improved after adding MFC; the tensile strength of the carbon fiber substrate without adding MFC in Comparative Example 1 is only 0.25 MPa, and the tensile strengths after adding MFC in Example 1 and Example 2 are 5.12 MPa and 10.34 MPa, respectively. When the addition amount accounts for 5% of the carbon fiber, the strength effect of the surface sizing in Comparative Example 2 can be achieved, and the bending strength also has the same trend; in terms of electrical properties, the resistivity of the carbon fiber substrate with MFC added in Example 1 is significantly lower than that of the carbon fiber substrate with surface sizing in Comparative Example 2, wherein the plane resistivity is reduced by about 61.47%, and the vertical resistivity is reduced by about 70.32%.

[0076] It can be seen from the data in Examples 4-6 that the carbon fiber substrate prepared after pretreatment of the reinforcing fibers has a higher uniformity, and different pretreatment methods will affect the performance of the carbon fiber substrate. Ultrasonic activation can make MFC more refined, expose more hydroxyl groups, and increase the connection between them and between the carbon fibers. Adding preoxidized silk pulp can bind the overlap of carbon fibers and carbon fibers, and the finer MFC will adhere to more preoxidized silk pulp, further improving its physical strength; MFC is protonated using a pretreatment solution with added proton acid to protonate the hydroxyl groups in the cellulose molecules, thereby improving the conductivity of the carbon fiber substrate; in Example 4, after ultrasonic treatment of MFC and preoxidized silk pulp in a pretreatment solution with added proton acid, the prepared carbon fiber substrate has the best effect. Compared with the carbon fiber substrate prepared by adding untreated MFC in Example 1, the plane resistivity is reduced by 44.50%, and the vertical resistivity is reduced by 16.61%.

[0077] (5) The mechanical strength and resistivity of the raw carbon paper prepared in Examples 7-12 and Comparative Examples 3, 4, and 5 were tested in accordance with the national standard GB / T20042.7-2014: "Proton Exchange Membrane Fuel Cell Part 7: Carbon Paper Characteristics Test Method". The test results are shown in Table 2.

[0078] Table 2

[0079] It can be seen from the data in Table 2 that the raw carbon paper prepared by adding untreated MFC in Example 7 and the raw carbon paper prepared by adding untreated MFC and preoxidized silk pulp in Example 8, compared with the raw carbon paper in Comparative Examples 3 and 5, have significantly improved physical strength, which is mainly attributed to the increase in the amount of sizing; compared with Comparative Example 3, the plane resistivity of Example 7 is reduced by 5.26%, and the vertical resistivity is reduced by 5.91%, that is, the addition of MFC can not only significantly improve the mechanical strength of the carbon fiber substrate and the raw carbon paper, but also improve the conductivity of the raw carbon paper; in Example 8, after adding preoxidized silk pulp, the mechanical strength and conductivity of the raw carbon paper are further improved. Compared with Comparative Example 3, the plane resistivity of Example 8 is reduced by 12.56%, and the vertical resistivity is reduced by 14.01%. This is because the conductivity of the preoxidized silk is improved after carbonization, which optimizes the conductive network of the raw carbon paper, and the loading amount of the preoxidized silk pulp after ultrasonic activation is greater, and the conductive performance is better.

[0080] By comparing Example 11 with Example 8, it can be seen that protonation pretreatment of the reinforcing fibers can improve the conductivity of the raw carbon paper; by comparing Example 12 with Example 8, it can be seen that ultrasonic treatment of the reinforcing fibers can significantly improve the tensile strength and flexural strength of the raw carbon paper, which is mainly due to the fact that MFC has more retention networks in the carbon fiber substrate and the resin sizing amount is higher; by comparing Example 9 with Example 8, it can be seen that ultrasonic treatment of MFC and preoxidized silk pulp in a pretreatment solution containing protonic acid can simultaneously improve the mechanical strength and conductivity of the raw carbon paper. The phenolic resin impregnated with graphite powder in Example 10 can further improve the conductivity of the raw carbon paper on the basis of ensuring high mechanical strength. Compared with the raw carbon paper obtained by surface sizing in Comparative Example 5, the planar resistivity of the raw carbon paper in Example 10 is reduced by 60.90%, and the vertical resistivity is reduced by 56.26%; compared with the raw carbon paper in Example 8, the planar resistivity of the raw carbon paper in Example 10 is reduced by 38.95%, and the vertical resistivity is reduced by 31.30%.

[0081] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.

Claims

1. A method for preparing a carbon fiber substrate for a fuel cell, characterized in that: The following steps are involved: S1. Using MFC or a mixture of MFC and pre-oxidized silk pulp as reinforcing fiber, the reinforcing fiber is mixed with water for beating to obtain a premixed slurry; S2. The carbon fiber, the premixed slurry and the dispersant are mixed to obtain a mixed slurry, and the mixed slurry is formed by a wet forming process and then dried to obtain the carbon fiber substrate.

2. The method for preparing a carbon fiber substrate for a fuel cell according to claim 1, characterized in that: In step S1, before preparing the premixed slurry, it also includes a step of performing a first pretreatment or a second pretreatment on the reinforcing fiber; The first pretreatment step includes: preparing a pretreatment solution containing protonic acid, organic solvent and water, and placing the reinforcing fiber in the pretreatment solution for immersion; or placing the reinforcing fiber in the pretreatment solution and performing ultrasonic treatment; The second pretreatment step includes placing the reinforcing fiber in water and performing ultrasonic treatment.

3. The method for preparing a carbon fiber substrate for a fuel cell according to claim 2, characterized in that: The first pretreatment specifically includes the following steps: placing the MFC in the pretreatment solution, ultrasonically activating for 40-60 minutes, then adding the preoxidized silk pulp, continuing ultrasonic treatment for 30-60 minutes, solid-liquid separation, freeze-drying, and obtaining the pretreated reinforced fiber.

4. The method for preparing a carbon fiber substrate for a fuel cell according to claim 2, characterized in that: Contains at least one of the following characteristics: (1) H in the pretreatment solution + The concentration is 0.15-2mol / L; (2) The protonic acid includes hydrochloric acid and / or sulfuric acid; (3) The organic solvent includes ethanol and / or acetone; (4) In the pretreatment liquid, the mass ratio of the organic solvent to the water is 1:1-3:

1.

5. The method for preparing a carbon fiber substrate for a fuel cell according to claim 1, characterized in that: In step S1, the beating speed is 5-30 m / s, and the beating time is 5-20 min.

6. The method for preparing a carbon fiber substrate for a fuel cell according to claim 1, characterized in that: Before step S2, the method further includes performing a third pretreatment on the carbon fiber, wherein the third pretreatment includes: performing air preoxidation treatment on the carbon fiber in an air atmosphere, wherein the air preoxidation treatment is performed at a temperature of 300-600° C. and a treatment time of 30-150 min.

7. The method for preparing a carbon fiber substrate for a fuel cell according to claim 1, characterized in that: In step S2, at least one of the following features is included: (1) The stirring speed of the mixing is 5-30 m / s, and the mixing time is 5-30 min; (2) In the mixed slurry, the mass concentration of the carbon fiber is 0.1%-0.5%; (3) The mass percentage of the MFC to the carbon fiber is 5%-10%; (4) The mass percentage of the pre-oxidized silk pulp to the carbon fiber is 0%-10%; (5) In the mixed slurry, the mass concentration of the dispersant is 0.1%-0.5%; (6) The dispersant includes at least one of polysorbate, polyurethane, and hydroxypropyl cellulose.

8. A carbon fiber substrate for a fuel cell, characterized in that: The carbon fiber substrate for fuel cells is prepared by the preparation method of any one of claims 1 to 7.

9. A method for preparing raw carbon paper for fuel cells, characterized in that: The following steps are involved: The raw carbon paper is obtained by using the carbon fiber substrate for fuel cells as claimed in claim 8, through resin impregnation, drying, hot pressing and curing, and carbonization and graphitization treatment.

10. A raw carbon paper for a fuel cell, characterized in that: The fuel cell carbon paper is prepared by the method for preparing raw carbon paper for fuel cells as claimed in claim 9.

Citation Information

Patent Citations

  • Preparation method of high-uniformity double-layer gradient pore carbon paper base paper

    CN115262278A

  • Microfibrillated cellulose with enhanced properties and methods of making same

    CN115961502A

  • Electrode material and its production process

    JP2008034557A

  • Method for manufacturing porous electrode base material and porous electrode base material

    JP2013118051A

  • Porous electrode substrate and manufacturing method thereof

    JP2018142449A

Cited By

  • Carbon paper for fuel cell and preparation method thereof

    CN119800773A